2021
DOI: 10.1186/s40317-021-00232-4
|View full text |Cite
|
Sign up to set email alerts
|

Wireless logging of extracellular neuronal activity in the telencephalon of free-swimming salmonids

Abstract: Background Salmonids return to the river where they were born in a phenomenon known as mother-river migration. The underpinning of migration has been extensively examined, particularly regarding the behavioral correlations of external environmental cues such as the scent of the mother-river and geomagnetic compass. However, neuronal underpinning remains elusive, as there have been no biologging techniques suited to monitor neuronal activity in the brain of large free-swimming fish. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Thus, Canfield and Mizumori [ 202 ] reported the presence of cells in the dorsolateral telencephalon of cichlids and goldfish that appear to display some location-specific discharge. Takahashi et al [ 203 ] described directionally tuned cells in the telencephalic pallium of rainbow trout that fired when the fish head was oriented in a specific direction. In a more comprehensive study, Vinepinsky et al [ 186 ] likewise showed the presence of cells with navigation-related activity in the dorsolateral telencephalon of free-swimming goldfish, for example, “border cells”, that increase their firing rate when the fish approaches the environmental boundaries, and “velocity cells”, whose activity correlate with the fish swimming direction and speed.…”
Section: Hippocampal Pallium Mechanisms For Map-like Spatial Navigation In Teleost Fishmentioning
confidence: 99%
“…Thus, Canfield and Mizumori [ 202 ] reported the presence of cells in the dorsolateral telencephalon of cichlids and goldfish that appear to display some location-specific discharge. Takahashi et al [ 203 ] described directionally tuned cells in the telencephalic pallium of rainbow trout that fired when the fish head was oriented in a specific direction. In a more comprehensive study, Vinepinsky et al [ 186 ] likewise showed the presence of cells with navigation-related activity in the dorsolateral telencephalon of free-swimming goldfish, for example, “border cells”, that increase their firing rate when the fish approaches the environmental boundaries, and “velocity cells”, whose activity correlate with the fish swimming direction and speed.…”
Section: Hippocampal Pallium Mechanisms For Map-like Spatial Navigation In Teleost Fishmentioning
confidence: 99%
“…This reflects the current situation of electric fish research which seems to focus more on aspects of electric communication and antagonistic behavior and its hormonal control (Perrone and Silva 2018;Metzen 2019;Dunlap et al 2021). The ability to monitor brain activity in freely swimming fish (Takahashi et al 2021;Cohen et al 2023) has a great potential for investigating electrolocation under more natural conditions in the future.…”
Section: Spatial Orientation Memory and Communication Are The Top 3 R...mentioning
confidence: 67%
“…Using a lightweight logger capable of wirelessly recording neural activity from the brain of freely behaving wild animals ( 30 ), we recorded neural activities in the brain of 10 wild streaked shearwater chicks before their first migration flight (Fig. 1, A and B; table S1; and figs.…”
Section: Resultsmentioning
confidence: 99%